A new design and simulation of cylindrical-gold horn Nano-antenna at terahertz region for energy harvesting application - Maryam Abbas Mohammed, Doaa; Mohammed Ali, Faris; M. Wadi, Salim (International Journal of Engineering and Technology, 2019)
In this paper, the design and simulate a new horn nanoantenna at terahertz frequencies by using the CST Microwave studio 2018. The proposed design be composed of an Au–Air–Au symmetric transmission line flared horn at the end, where the arranged of cylindrical gold pillars have been considered in the geometrical lattice. The Numerical simulation have been done in this work with taking in the consideration the losses of the material and the desperation. The horn nanoantenna shown with numerical results (wide bandwidth) and the directivity is greater than 10 dB from the results, the horn nanoantenna could be used in different applications such as energy harvesting, telecommunication and different technical ranging from smart lighting to optical wireless communication.